2007
DOI: 10.1007/s00427-007-0148-1
|View full text |Cite
|
Sign up to set email alerts
|

A NLRR-1 gene is expressed in migrating slow muscle cells of the trout (Oncorhynchus mykiss) embryo

Abstract: NLRR-l (neuronal leucine-rich repeat-l) is a transmembrane protein that functions as a cell adhesion molecule regulating morphogenesis. A previous study in the mouse reported that the somitic expression of NLRR-1 is restricted to the dorsal lip of the dermomyotome that gives rise to the epaxial muscle. In this study, we report the expression of a NLRR-1 gene in the trout-developing somite. Whole mount in situ hybridization showed that NLRR-l transcript accumulated in a rostro-caudal wave in the adaxial slow mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…In trout‐developing somite, N‐cadherin expression is clearly excluded from slow muscle cells as soon as they start their migration toward the most lateral surface of the myotome. On the other hand, we have previously shown that NLRR‐1, which also encodes an immunoglobulin‐like domain containing transmembrane protein, is specifically expressed in migrating slow cells suggestive of a role for NLRR‐1 in slow cell morphogenesis in trout (Dumont et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In trout‐developing somite, N‐cadherin expression is clearly excluded from slow muscle cells as soon as they start their migration toward the most lateral surface of the myotome. On the other hand, we have previously shown that NLRR‐1, which also encodes an immunoglobulin‐like domain containing transmembrane protein, is specifically expressed in migrating slow cells suggestive of a role for NLRR‐1 in slow cell morphogenesis in trout (Dumont et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…À propos des progéniteurs cellulaires du myotome embryonnaire, il est intéressant de noter des traits qui sont communs aux cellules de la lèvre dorsomédiane du dermomyotome des amniotes et aux cellules adaxiales du poisson. En effet, les cellules adaxiales comme les cellules de la lèvre dorsomédiane sont les premières à exprimer les MRF et à se différencier ; elles expriment le gène NLRR-1 (neuronal leucine-rich repeat-1) qui code une molécule transmembranaire impliquée dans l'adhérence cellulaire [20], et enfin elles sont programmées pour former des fibres musculaires dont le phénotype est essentiellement lent [21].…”
Section: Croissance Du Myotome Embryonnaire à Partir De L'épithélium unclassified